Magnesium sulfate treatment for juvenile ferrets following induction of hydrocephalus with kaolin. Issue 1 (December 2016) - Curzio, Domenico; Turner-Brannen, Emily; Mao, Xiaoyan; Bigio, Marc
Abstract Background Previous work with 3-week hydrocephalic rats showed that white matter damage could be reduced by the calcium channel antagonist magnesium sulfate (MgSO4 ). We hypothesized that MgSO4 therapy would improve outcomes in ferrets with hydrocephalus induced with kaolin at 15 days. Methods MRI was performed at 29 days to assess ventricle size and stratify ferrets to treatment conditions. Beginning at 31 days age, they were treated daily for 14 days with MgSO4 (9 mM/kg/day) or sham saline therapy, and then imaged again before sacrifice. Behavior was examined thrice weekly. Histological and biochemical ELISA and myelin enzyme activity assays were performed at 46 days age. Results Hydrocephalic ferrets exhibited some differences in weight and behavior between treatment groups. Those receiving MgSO4 weighed less, were more lethargic, and displayed reduced activity compared to those receiving saline injections. Hydrocephalic ferrets developed ventriculomegaly, which was not modified by MgSO4 treatment. Histological examination showed destruction of periventricular white matter. Glial fibrillary acidic protein content, myelin basic protein content, and myelin enzyme activity did not differ significantly between treatment groups. Conclusion The hydrocephalus-associated disturbances in juvenile ferret brains are not ameliorated by MgSO4 treatment, and lethargy is a significant side effect.